Dataset for Repeated Measures ANOVA and Adjusted F-Tests When Sphericity is Violated: Which Procedure is Best? - Blanca-Mena, María José; Arnau Gras, Jaume; García-de-Castro, Fernando Javier; Alarcón-Postigo, Rafael; Bono Cabré, Roser (Universidad de Málaga, 2024)
Tables correspond to the performance of the F-statistic, and of F adjusted by the Greenhouse-Geisser (F-GG) and Huyhn-Feldt (F-HF) procedures in terms of Type I error and power in repeated measures designs with normal data. Values of epsilon are fixed according to the Greenhouse–Geisser procedure. The number of repeated measures (3, 4, and 6), sample size (from 10 to 300), and epsilon values (from the lower to its upper limit) were manipulated.
Keywords: Psicología - Investigación; Análisis de varianza; Robustness; Type I error; Power